Music and reading activities in early childhood associated with improved language development in preterm infants at 2–3 years of age - Kostilainen, Kaisamari; Fontell, Noora; Mikkola, Kaija; Pakarinen, Satu; Virtala, Paula; Huotilainen, Minna; Fellman, Vineta; Partanen, Eino (Frontiers in Psychology, 2024)
Introduction Children born preterm are at increased risk for adverse neurodevelopmental outcomes. Music and reading activities in childhood could ameliorate these difficulties, as they have shown benefits on both neural and behavioral levels. However, only a few studies have assessed these potential benefits in preterm-born children. We investigated whether music and language activities in early childhood are associated with improved developmental outcomes of preterm-born children. Methods The cognitive, language, and motor skills of 45 children, born between 24 and 34 gestational weeks, were tested at 23–38 months of corrected age with the Bayley Scales of Infant and Toddler Development, Third Edition. Background information, including parental education, and the weekly amount of music and language-related activities was collected using parental questionnaires. Results The amount of singing, playing musical instruments and reading aloud was associated with better language skills. Moreover, children who had participated in a music playschool had better language skills when compared to those children who had not participated in a music playschool. Maternal education was associated with music playschool participation and better language and motor skills in children attending music playschool. Discussion Interactive music and language activities in early childhood may improve language skills in preterm-born children. Informing and guiding parents at an early stage to integrate these activities into their daily lives could be a one way of supporting the development of preterm-born children.